2019
DOI: 10.4149/bll_2019_120
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma levels of 25(OH)D in multiple sclerosis patients. Correlation with disease severity expressed by EDSS, MSSS, progression index and Herbert´s scale severity grade

Abstract: OBJECTIVES: Multiple sclerosis is a chronic infl ammatory and autoimmune demyelinating disease of the brain and spinal cord. Vitamin D has anti-infl ammatory and anti-Th1, Th17 activities, activates the function of regulatory T cells, shifts the immune response towards Th2, so it might be favorable for downregulation of the disease pathogenesis, and if infl ammation and Th1 and Th17 immunity are hyperactivated. The aim of our study was to highlight the role of vitamin D in multiple sclerosis pathogenesis. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This suggest that HMGB1 may play a dual role in neurodegenerative diseases; pro-inflammatory/neurotoxic and anti-inflammatory/neuroprotective role. However, in multiple sclerosis, contradictory HMGB1 expression has been concluded, where some studies showed no significant increase in HMGB1 expression [ 67 , 71 , 72 , 74 ], whereas others showed a significant increase in expression [ 67 , 69 , 70 , 73 , 79 ]. This contradiction in HMGB1 levels may be related to the stage of the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that HMGB1 may play a dual role in neurodegenerative diseases; pro-inflammatory/neurotoxic and anti-inflammatory/neuroprotective role. However, in multiple sclerosis, contradictory HMGB1 expression has been concluded, where some studies showed no significant increase in HMGB1 expression [ 67 , 71 , 72 , 74 ], whereas others showed a significant increase in expression [ 67 , 69 , 70 , 73 , 79 ]. This contradiction in HMGB1 levels may be related to the stage of the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although vitamin D and its derivatives have been shown to have signi cant anti-carcinogenic properties (Bucova et al 2019;; , epidemiological studies have found little consistent evidence supporting a protective association between high plasma 25(OH)D and PC incidence and mortality. Ecological studies of latitudinal changes and UVB radiation (Mohr et reporting an elevated risk for PC among those with higher plasma 25(OH)D. Given the con icting epidemiologic ndings, we therefore systemically searched and analyzed all available literature to explore the updated results on the association between plasma 25(OH) D and PC incidence and mortality.…”
Section: Introductionmentioning
confidence: 99%